Seasonal Dynamics of Non-Biting Midges (Diptera: Chironomidae) and Relevant Environmental Factors - Teng Lei; Jingjing Gu; Mengyao Zhao; Yuqiu Chen; Chao Song; Xin Qi (Insects, 2024)
The family Chironomidae is speciose and is present in almost all freshwater habitats. Adult non-biting midges emerge from waterbodies and swarm in high numbers, occasionally disrupting people’s outdoor activities. In order to understand the seasonal dynamics of species composition, a continuous observation of non-biting midge diversity was performed. Adult non-biting midges were collected using light traps from the autumn of 2022 to the summer of 2023 in an urban wetland park. Species were identified based on morphological characteristics and DNA barcodes. Alpha diversity was evaluated using Margalef, Pielou, and Shannon–Wiener indexes. Beta diversity was evaluated using unconstrained NMDS analysis and constrained CCA. The impacts of environmental factors, including barometric pressure, temperature, relative humidity, and wind speed, on the variation in species composition were estimated in the constrained analyses. A total of 42 species were identified, with 29 species belonging to Chironominae, 9 species belonging to Orthocladiinae, and 4 species belonging to Tanypodinae. The species composition varied across different seasons. Summer sites and autumn sites shared the highest similarity in diversity, and spring sites presented the lowest diversity. The variation was significantly correlated with environmental conditions. The results showed that seasonality is a factor influencing the diversity of adult non-biting midges.